Methodology for selecting criterion and analysis of electromagnetic compatibility of groups of radio electronic equipment in mobile communication networks - Коляденко, Ю.Ю.; Чурсанов, М.О. (Radiotekhnika, 2020)
For many electronic devices, the parameters of useful signals, noise and interference are random and often non-stationary processes with unknown current characteristics. The frequency spectra of useful signals and interference are usually different, with varying degrees of overlap. All this has led to a variety of criteria and ambiguity in the assessment of EMC. A review of the criteria for electromagnetic compatibility in groups of electronic devices. It is proposed at the design stage of mobile communication networks to use the criterion of channel capacity, which takes into account the total interference power. When refarming the radio frequency spectrum, it is proposed to use the criterion of energy equivalence. Refarming of the radio frequency spectrum requires the development of conditions for the joint functioning of networks of several standards in adjacent frequency bands within the same range. The criterion allows you to determine the conditions for maintaining the energy equivalence of a network with outdated technology in the frequency band of the appropriate width to create a network with new technology, namely: calculate the allowable number of transmitters of the new network; evaluate (if necessary) the necessary limitation of the radiation power of the transmitters of the new network. This criterion makes it possible to assess accurately the electromagnetic environment and is easy to use. At the stage of functioning of the mobile communication network, it is proposed to use the criterion of the ratio of the useful signal power to the total interference and noise power. It is proposed to evaluate this criterion from the results of measurements in real time. The presented methodology for selecting the criterion and analysis of EMC allows a qualitative and quantitative analysis of the electromagnetic environment and the quality of communication in radio access systems with multi-frequency signals, both at the design stage, refarming, and at the stage of network operation.